The role of marketing information in enhancing market share: A study on a sample of service institutions in the city of Baghdad - Al-Azzawi, Hameed Shukur AbdulAmeer; Ahmed, Hasanain Hamid; Ali, Mohammed Hussein; Jabbar, Riyadh Hassoon (Edelweiss Applied Science and Technology, 2025)
The research problem is summarized by measuring the availability of marketing information and its role in enhancing the market share of service institutions, with an indication of the most important information that can be adopted to enhance market share in service institutions. The descriptive analytical approach has been adopted in the research, and the questionnaire was distributed to 130 managers in the market share of service establishments. The analysis of the questionnaire results relied on the SPSS program. The statistics have proven significant effects of knowledge in various fields on market share. Market share knowledge accounts for 23.4% variance (R² = 0.234), and it has a regression coefficient of 0.484 with a t-value of 4.972. Customer knowledge accounts for 29.5% of the variance, while environmental knowledge covers 36.5%. Supplier and service knowledge also explained the variance, with service knowledge accounting for 39.8%. Thus, the arguments proposed above articulate the importance of knowledge in explaining market share dynamics and highlight that the concept of knowledge is strategically important for market success.